Combinatorial aspects of commutative algebra and algebraic geometry the Abel Symposium 2009 - Floystad, Gunnar (Abel symposia, 2011)
Abel Symposium 2009 Combinatorial aspects of Commutative Algebra and Algebraic Geometry, held at Voss, Norway, featured talks by leading researchers in the field.  This is the proceedings of the Symposium, presenting contributions on syzygies, tropical geometry, Boij-Soderberg theory, Schubert calculus, and quiver varieties. The volume also includes an introductory survey on binomial ideals with applications to hypergeometric series, combinatorial games and chemical reactions.   The contributions pose interesting problems, and offer up-to-date research on some of the most active fields of commutative algebra and algebraic geometry with a combinatorial flavo